Familial risk of venous thromboembolism in first-, second- and third-degree relatives: a nationwide family study in Sweden - Zöller, Bengt; Ohlsson, Henrik; Sundquist, Jan; Sundquist, Kristina (Thrombosis and Haemostasis, 2013)
Venous thromboembolism (VTE) clusters in families, but the familial risk of VTE has only been determined in first-degree relatives. This nationwide study aimed to determine the familial risk of VTE in first-, second- and third-degree relatives of affected individuals. The Swedish Multi-Generation Register was linked to Hospital Discharge Register data for the period 1987–2009. This was a case-cohort study. Odds ratios (ORs) for VTE were calculated for individuals whose relatives were hospitalised for VTE, as determined by the International Classification of Diseases (ICD), and those whose relatives were unaffected by VTE. The familial OR for VTE was 2.49 in siblings (95% confidence interval [CI] 2.40–2.58), 2.65 in children (2.50–2.80), 2.09 in parents (2.03–2.15), 1.52 in maternal half-siblings (1.26–1.85), 2.34 in paternal half-siblings (2.00–2.73), 1.69 in nieces/nephews (1.57–1.82), 1.47 in cousins (1.33–1.64), and 1.14 in spouses of individuals diagnosed with VTE (1.09–1.18). Familial clustering was stronger at young ages. The familial transmission was slightly stronger for males compared with females but was only significant for siblings 1.13 (1.05–1.22) and parents 1.11 (1.05–1.78) of probands. The present data showing an increased VTE risk among not only first-degree relatives but also second- and third-degree relatives indicate that the genetic component of the familial clustering of VTE is strong. Family history is a potentially useful genetic surrogate marker for clinical VTE risk assessment, even in second- and third degree-relatives.
Keywords: Thrombophilia; deep venous thrombosis; risk factors; thrombosis; epidemiological studies